TRANSLANGUAGING PRACTICES AND RECONTEXTUALIZING LEARNING MATERIAL: A CORPUS-BASED STUDY OF GLOBAL CHINESE LANGUAGE TEXTBOOKS USED IN SRI LANKA - Yasasri, Noel Sampath (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Despite the abundance of studies investigating translanguaging pedagogy, recontextualizing learning material has rarely been a concern of recent studies. The present study employs content analysis and critical discourse analysis to examine two global CFL textbooks used in Sri Lanka to evaluate their compliance with translanguaging practices. Three imperative aspects of translanguaging pedagogy, namely representation of culture, instruction language, and nationalism and socio-cultural polarization were the key areas of concern in content analysis. In the culture domain analysis, references from the textbooks were fed into 10 child codes and 3 parental codes in NVivo12. The results demonstrated that there is a critical inequity in the representation of local and global cultures in the textbooks which is especially distinct in the interlocutors and their nationality options. Socio-cultural polarization of the source culture with the West was evident in the critical discourse analysis and adaptation was predominantly promoted as a unilateral affair where the foreign learner continually adapts to the target culture. The study proposes that contextual sensitivity and ideological impartiality should be ensured in recontextualizing textbooks for translanguaging practices in Sri Lanka from three aspects, namely incorporation of L1 into textbooks, integration of multiculturalism and freeing textbooks of ideological and hegemonic practices.